2017
DOI: 10.1016/j.kjms.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal surgery improves oral health‐related quality of life in chronic periodontitis patients in Asian population

Abstract: The effect of periodontal surgery on patients' quality of life was investigated. Sixty patients received regenerative surgery or resective osseous surgery. Oral health-related quality of life and health-related quality of life instruments were used to assess the participants' quality of life before surgery and 4 weeks after surgery. Periodontal surgery can improve patients' quality of life by alleviating the physical pain and psychological discomfort. The scores were lower (more favorable) in the regenerative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Non-surgical therapy and regenerative surgical therapy utilizing EMD showed better results regarding the OHRQoL than surgical therapy alone, although this improvement and in general the findings of this study were limited only to the first week postoperatively. The effect of periodontal surgery on quality of life was studied by Chou et al [30], who reported a significant improvement after a surgical approach to periodontal defects. A more favorable result was reported for regenerative surgery in comparison to respective surgery, although this study did not evaluate the effect of initial periodontal therapy on the quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-surgical therapy and regenerative surgical therapy utilizing EMD showed better results regarding the OHRQoL than surgical therapy alone, although this improvement and in general the findings of this study were limited only to the first week postoperatively. The effect of periodontal surgery on quality of life was studied by Chou et al [30], who reported a significant improvement after a surgical approach to periodontal defects. A more favorable result was reported for regenerative surgery in comparison to respective surgery, although this study did not evaluate the effect of initial periodontal therapy on the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to them, while periodontal disease was associated with a negative impact on OHRQoL [13][14][15][16][17][18], initial periodontal therapy was associated with an improvement [19][20][21][22][23][24][25][26]. In terms of surgical periodontal treatment, there is a limited number of studies evaluating the influence of periodontal surgery indicating that it has a lesser effect on QoL [12,[27][28][29][30]. Additionally, taking into account that different populations may be characterized by different cultural and behavioral aspects, QoL alterations after periodontal therapy may vary among different nations or geographic ranges.…”
Section: Introductionmentioning
confidence: 99%
“…White et al reported that after the third molar surgery, it took an average of three days to get back to daily activities and social life and five to seven days to get over the inability to chew properly and get back on a regular diet [ 18 ]. Chou et al found that there was a significant (moderate) difference between pre- and post-surgery physical pain (psychological discomfort) scores among their study participants [ 19 ]. Saito et al reported that there was a significant difference between the QoL of periodontal surgery patients before and after treatment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…How effective is periodontal therapy in elderly, it is certainly worth while treating periodontal disease in elderly with high quality treatment combined with adequate plaque control and motivation to result in a good therapeutic outcome. 20,21 The literature suggest that age per se is not an important factor in determining the result of periodontal therapy. 19…”
Section: Case Reportmentioning
confidence: 99%